A comparative study of shift work effects and injuries among nurses working in rotating night and day shifts in a Tertiary Care Hospital of North India - Anjana Verma; Jugal Kishore; Shobha Gusain (Wolters Kluwer Medknow Publications, 2018)
Background: Shift work can have an impact on the physical and psychological well-being of the healthcare worker, affecting patients as well as their own safety at the workplace. This study was conducted to compare the health outcomes and injuries, along with associated risk factors between the nurses working in rotating night shift (RNS) as compared to day shift (DS) only. Materials and Methods: It was a cross-sectional study conducted from June to November 2016 in a tertiary care hospital of Delhi. It involved 275 nurses working in RNS and 275 nurses from DS of various departments, selected through simple random sampling. Standard Shift Work Index Questionnaire (SSI) was used as the study instrument, with selected variables (according to objectives of the study). Data were analyzed using descriptive statistics, Chi-square, t-test, and multivariate regression. Results: Female nurses had more sleep disturbance, fatigue, and poor psychological health. Working on a contractual basis, RNS, and living outside the hospital campus were associated with higher odds of having needle stick injury (NSI).The nurses working in RNSs were found to have significantly lower mean scores in job satisfaction (p = 0.04), sleep (p < 0.001), and psychological well-being (p = 0.047) as compared to DS workers. Conclusions: Health outcomes among nurses working in RNSs call for the interventions, focused on various factors which can be modified to provide supportive and safer working environment.